2016
DOI: 10.1007/s13277-016-5074-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 promotes cell proliferation, migration, and resistance to apoptosis through PTEN/PI3K/AKT signaling pathway in esophageal cancer

Abstract: Our study aimed to explore associations between microRNA-21 (miR-21) and PTEN/PI3K/AKT signaling pathway and, further, to elucidate the regulation of miR-21 on biological behaviors in human esophageal cancer cells. The expressions of miR-21, PTEN, PI3K, and AKT were detected in 89 esophageal cancer samples and 58 adjacent normal tissues respectively. The human esophageal cancer cells (TE11) were grouped as following: blank (TE11 cells without transfection), negative (TE11 cells with miR-21 negative inhibitor),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 27 publications
1
75
0
Order By: Relevance
“…PTEN is associated with the occurrence of several types of tumor, and serves an important role in tumor cell growth, apoptosis, adhesion, migration and invasion (5). Previous studies have revealed that the downregulation or deletion of PTEN activates the phosphoinositide 3-kinase/RAC-α serine/threonine-protein kinase (PI3K/AKT) signaling pathway, resulting in the occurrence, development, invasion and metastasis of cancer (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is associated with the occurrence of several types of tumor, and serves an important role in tumor cell growth, apoptosis, adhesion, migration and invasion (5). Previous studies have revealed that the downregulation or deletion of PTEN activates the phosphoinositide 3-kinase/RAC-α serine/threonine-protein kinase (PI3K/AKT) signaling pathway, resulting in the occurrence, development, invasion and metastasis of cancer (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor-suppressor PTEN is a well-known target of the miR-21-5p[43], and thus we aimed at addressing whether modulation of PTEN may influence our conclusion in this experimental system. First, we found that metformin treatment reduced colony formation and migration of the PTEN-devoid BT-549 cells (Figure 5a and b, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…PTEN gene mutation or deficiency and abnormal protein expression can promote cell proliferation and inhibit cell apoptosis, the expression of PTEN in malignant tumors is negatively correlated with tumor TNM staging, and meantime, the low expression of PTEN is closely related to chemotherapy resistance of breast cancer (Song et al, 2016); (Wu et al, 2016). In this study, the author has observed that the expression of PTEN in cells can be induced by silencing the expression of CD164 in U87 cells, so it is suspected that the apoptosis of glioma cells induced by CD164shRNA may be related to PTEN pathway.…”
Section: Discussionmentioning
confidence: 99%